Dietary nitrate improves muscle microvascular reactivity and lowers blood pressure at rest and during isometric exercise in untreated hypertensives. (11th January 2019) - Zafeiridis, Andreas; Triantafyllou, Areti; Papadopoulos, Stavros; Koletsos, Nikolaos; Touplikioti, Panagiota; Zafeiridis, Alexandros S.; Gkaliagkousi, Eugenia; Dipla, Konstantina; Douma, Stella
Abstract: Objective: This double‐blind, cross‐over study examined in drug‐naïve hypertensives the effects of a single dose of dietary nitrate (beetroot juice, BRJ) on (a) office/ambulatory BP and arterial stiffness, (b) muscle microvascular function, and (c) hemodynamic responses and cardiovagal baroreceptor sensitivity (cBRS) at rest and during isometric exercise. Methods: Eighteen untreated hypertensives (44.0 ± 2.6 years) consumed randomly, a nitrate‐rich (8.1 mmol‐BRJnitrate ) and a nitrate‐depleted (BRJplacebo ) BRJ. Office BP and pulse wave velocity were assessed before/after BRJ. An occlusion‐reperfusion maneuver with continuous monitoring of muscle oxygenated hemoglobin (O2 Hb) and total hemoglobin (tHb), via NIRS, followed. Participants performed submaximal isometric handgrip with beat‐by‐beat monitoring of hemodynamics and cBRS. Ambulatory BP assessment followed. Results: During reperfusion, following arterial occlusion, the magnitude and rate of muscle microvascular reoxygenation (O2 Hb) and red blood cell content (tHb) were higher in BRJnitrate vs BRJplacebo ( P  < 0.05), suggesting improved microvascular reactivity. Office/ambulatory BP were lower following BRJnitrate vs BRJplacebo ( P  < 0.05); pulse‐wave‐velocity was not altered. During isometric handgrip, BP and peripheral resistance rise were smaller in BRJnitrate vs BRJplacebo ( P  < 0.01‐0.05), with no differences in cBRS. Conclusions: In drug‐naïve hypertensives, a single dose of BRJ induces (a) short‐term reductions in resting/ambulatory BP, (b) acute improvements in muscle microvascular function, and (c) attenuation in BP and peripheral resistance responses during isometric exercise.